A novel nitrogen-rich phosphinic amide towards flame-retardant, smoke suppression and mechanically strengthened epoxy resins. (February 2022) - Liu, Xin-Duo; Zheng, Xian-Ting; Dong, Ying-Qi; He, Ling-Xiang; Chen, Feng; Bai, Wei-Bin; Lin, Yu-Cai; Jian, Rong-Kun
Highlights: Nitrogen-rich tetrazole was phosphorylated to chemically modify epoxy resin (EP). The modified EP exhibited remarkable smoke suppression and flame retardancy. The modified EP presented strengthened mechanical properties. Abstract: In this work, aiming to obtain multifunctional epoxy resin (EP) possessing flame retardancy and light smoke without compromising the mechanical properties, a novel nitrogen-rich phosphinic amide named D -5-AT was synthesized and then incorporated to EP. The results showed that UL-94 V-0 rating of EP with 7.5 wt% D -5-AT was available and limiting oxygen index (LOI) was up to 35.1%. Meanwhile, in the presence of D -5-AT, the heat release and smoke production of EP/D-5-AT materials were effectively suppressed during combustion as compared with EP. The improvement mentioned above was found related to the condensed and gaseous flame retardant effect of D -5-AT through the investigation on char residues of EP/D-5-AT materials and volatiles of D -5-AT. Besides, because of the existence of more hydrogen bonds and bulky group by virtue of the introduction of D -5-AT, the mechanical properties of modified EP were strengthened as well. This work offered a promising method to meet the ever-increasing requirement of multi-functionality of epoxy resins.